Electromagnets arrangement for electromagnetic windshield wipers - Proposal and analysis - Mushtaq, S. (Asian Research Publishing Network, 2016)
The objective of this paper is to analyse the superior electromagnet placement to apply strong forces on the corresponding magnets used as automotive windshield wipers with different configuration as a replacement to conventional motors. The electromagnetics are engaged to observe the solenoids attraction and repulsive forces of the whole system with changing polarities. Main focus as pre-analysis is either side by side electromagnets or face to face electromagnets provides higher output force for this design. The observation is made based on flux along the moment arm and strength between the magnets. It was observed that face to face magnetic arrangement provides higher torque output on both of these parameters. Â© 2006-2016 Asian Research Publishing Network (ARPN).